SERVICE QUALITY ANALYSIS - HOTEL ALPIN (POIANA BRASOV) - MADAR ANCA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2013)
Hotel Alpin was built in 1971 in Poiana Brasov resort and has a 4 star quality ranking at the moment with the apart hotel having a 5 stars ranking. At the moment in the tourism market the service quality and client satisfaction are very important for being successful. This paper is analyzing through market research, clients’ satisfaction towards the service quality provided by Hotel Alpin. The purpose of this research is to validate the reputation of the hotel.